Rejoinder: race scholarship and the future. Issue 3 (19th February 2016) - Murji, Karim; Solomos, John
ABSTRACT: In this Rejoinder we seek to address the key issues raised by the four commentaries on our edited book. We focus on the question of the shifting boundaries of the field of race and ethnic studies, the absences and gaps in what is covered, the limits of the post-racial, and the whitening of sociology. In conclusion, we suggest some alternative ways in which we would seek to address them.